Design method of low-cost titanium alloy easy to thermally process
By establishing a model of the Ti-6Al-xV-yFe alloy system, the alloy composition is optimized, and the problem of poor thermal processing performance of Ti-6Al-4V alloy is solved, achieving low-cost and efficient thermal processing performance improvement.
Patent Information
- Application Number
- CN202510569539.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-03
- Publication Date
- 2025-08-15
AI Technical Summary
The existing Ti-6Al-4V alloy has poor thermal processing performance, complex processing process, low material yield, high cost, and the addition of Fe elements needs to be explored through experiments, resulting in waste of manpower and material resources and unstable performance.
By establishing a Ti-6Al-xV-yFe alloy system, combining Zener-Hollomon parameters and Hall-Petch enhancement model, a relationship model of β-stable element concentration, grain size and thermal processing parameters was established, the alloy element concentration was calculated, and the alloy composition was optimized to improve thermal processing performance.
Under the target thermal processing conditions, the alloy element concentration is directly calculated, the processing process is shortened, the cost is reduced, and the thermoplastic properties are improved, which avoids the drawbacks of traditional test methods and ensures the stability of alloy performance.
Smart Images

Figure CN120496706A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of titanium alloy materials, and in particular to a design method for a low-cost and heat-processable titanium alloy. Background Art
[0002] Due to their outstanding advantages such as lightweight, high specific strength, and high corrosion resistance, titanium alloys are widely used in a variety of fields, including marine vessels, deep-sea equipment, and biomedicine. With the rapid development of my country's aerospace and marine engineering industries, the demand for titanium alloys has become increasingly complex, and these demands are based on the thermoplasticity and hot working properties of titanium alloys. Therefore, the further development and application of titanium alloys has always been a research hotspot in the field of metal materials.
[0003] Ti-6Al-4V alloy is currently the most widely used titanium alloy material, accounting for 50% of the total titanium alloy usage each year. Currently, the most important forming process for Ti-6Al-4V alloy still relies on traditional high-temperature forging and hot rolling, including processes such as blanking, upsetting, drawing, punching, expanding, and bending. However, compared with metal materials such as aluminum and steel, Ti-6Al-4V alloy has complex processing and production processes and low yield rates. Its shortcomings such as high rheological resistance during hot working, difficult forming, and cumbersome hot deformation processing have greatly limited its application. In addition, the large amount of residual titanium generated during the production process indirectly increases the cost of using titanium alloys, especially in the civilian field. Therefore, improving the thermoplastic properties of Ti-6Al-4V alloy, shortening the processing flow of titanium alloys as much as possible, and reducing the cost of hot working of titanium alloys are the current research focuses of titanium alloys.
[0004] Numerous practical and theoretical studies have shown that microalloying is an effective way to improve the properties of titanium alloys. Studies on titanium-iron binary alloys have shown that the addition of Fe can effectively reduce the deformation resistance of titanium alloys during processing. Therefore, the thermoplastic properties of Ti-6Al-4V alloys can be improved by adding Fe.
[0005] However, in the Ti-6Al-4V alloy system, if too little Fe is added, it cannot effectively reduce the deformation resistance of the titanium alloy during processing. Adding too much will easily change the Ti-6Al-4V alloy system, making it unusable. Moreover, the same alloy will exhibit different hot working properties under different hot working conditions.
[0006] Therefore, in the actual production process, the amount of Fe element added is generally explored through a series of tests, and when the hot working conditions are changed, the amount of Fe element added needs to be explored again, which leads to a waste of manpower and material resources. At the same time, it is also easy to cause the problem of changes in the Ti-6Al-4V alloy system, thereby changing the performance of the alloy, which is not conducive to the promotion of the application of related materials. Summary of the Invention
[0007] The purpose of the present invention is to address the deficiencies of the existing technology and provide a design method for a low-cost, easily heat-processable titanium alloy. Under target heat processing conditions, the composition of the titanium alloy is directly determined through theoretical calculations, thereby improving the heat processing performance of the titanium alloy without changing the alloy properties.
[0008] According to the purpose of the present invention, a method for designing a low-cost, heat-processable titanium alloy is provided, comprising the following steps:
[0009] Establish the Ti-6Al-xV-yFe quaternary alloy system; then
[0010] The constraint relationship between the concentration of β-stabilizing elements and the β-stabilizing coefficient in Ti-6Al-xV-yFe alloy was established, and the first equation was obtained;
[0011] The Zener-Hollomon parameters were used to establish the relationship model between the average grain size of Ti-6Al-xV-yFe alloy after hot working and the concentration of β-stabilizing elements and hot working parameters, and the second equation was obtained;
[0012] The mechanical property strengthening model was established by combining the grain refinement strengthening and solid solution strengthening mechanisms, and the third equation was obtained;
[0013] According to the target yield strength and the target hot working conditions, the first equation, the second equation and the third equation are combined to obtain the corresponding concentration of the β-stabilizing element, thereby obtaining the desired alloy.
[0014] As an optional implementation, the first equation is shown as formula (1):
[0015] 15K β =x+3y (1)
[0016] Where, x is the mass percentage of V element in Ti-6Al-xV-yFe alloy; y is the mass percentage of Fe element in Ti-6Al-xV-yFe alloy; K β is the β stability coefficient of Ti-6Al-xV-yFe alloy, and its value is 0.27.
[0017] As an optional implementation, the second equation is shown as formula (2):
[0018]
[0019] Where, d is the average grain size of the alloy after hot working, μm; d0 is the average grain size before hot working, μm; α is the recrystallization inhibition coefficient of the alloy element, ranging from 0.35 to 0.55; K β is the β stability coefficient of Ti-6Al-xV-yFe alloy, which is 0.27; Z0 is the reference Z parameter, which is 10 12 s -1 ;β is the strain rate sensitivity index; Where ε is the strain rate, s -1 ; Q is the deformation activation energy, J / mo; R is the gas parameter, J / (mol·K); T is the hot working temperature, K.
[0020] As an optional embodiment, the relationship between the deformation activation energy Q and x, y is shown in formula (3):
[0021] Q=340-15x 0.5 -25y+0.8xy (3).
[0022] As an optional implementation, the third equation is shown in formula (4):
[0023] σ y =σ base +△σ soild +△σ Hall (4)
[0024] Where, σ y is the yield strength of the required Ti-6Al-xV-yFe alloy, MPa; σ base is the yield strength of Ti-6Al matrix, MPa; Δσ solid is the solid solution strengthening term, MPa; Δσ Hall is the Hall-Petch strengthening term, MPa.
[0025] As an optional embodiment, Δσ solid Determine by formula (5):
[0026]
[0027] Where M is the Taylor factor, dimensionless; G is the shear modulus, GPa; b is the Burgers vector, nm; η i is the distortion coefficient of the solute element, dimensionless; c i is the concentration of the solute element, wt.%.
[0028] As an optional embodiment, Δσ Hall Determine by formula (6):
[0029] △σ Hall =K d ×d -12 (6).
[0030] Where K d is the Hall-Petch coefficient, MPa·μm 1 / 2 ; d is the average grain size of the alloy after hot working, μm.
[0031] As an optional implementation, the target yield strength is determined as follows:
[0032] Substitute x=4, y=0 into the first, second, and third equations, and calculate the corresponding yield strength σ1 under the target hot working conditions. The target yield strength σ y The value of is controlled within σ1+1≤σ y It can be within the range of ≤σ1+10.
[0033] As an optional embodiment, after obtaining the desired alloy, a series of alloys with different y values are designed based on the determined y value, and then the first equation, the second equation and the third equation are combined to obtain the corresponding yield strength under the same target hot working conditions, thereby selecting an alloy with optimal strength and optimal hot working performance.
[0034] It can be seen from the above technical solutions of the present invention that the design method of low-cost and easy-to-heat-process titanium alloy proposed in the present invention links the alloy composition, grain size, processing technology and mechanical properties to establish a constitutive equation, so that under the target hot processing conditions, according to the target mechanical strength of the alloy, the corresponding alloy element concentration can be directly calculated through the established equation, thereby improving the hot processing performance of the titanium alloy without changing the alloy properties, thereby providing theoretical guidance for the composition design of the titanium alloy system, shortening the processing flow of the titanium alloy, and reducing the hot processing cost of the titanium alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a flow chart of the design method of the low-cost and heat-processable titanium alloy of the present invention.
[0036] Figure 2 1 and 2 are microstructure diagrams of alloy samples in examples of the present invention; wherein a is Ti-6Al-4V and b is Ti-6Al-3.1V-0.3Fe.
[0037] Figure 3 : is the peak stress curve of the alloy sample in the example of the present invention; wherein a is Ti-6Al-4V; b is Ti-6Al-3.1V-0.3Fe.
[0038] Figure 41 is a microstructure diagram of the alloy sample in the example of the present invention; wherein, a is Ti-6Al-2.2V-0.6Fe; b is Ti-6Al-1.3V-0.9Fe; c is Ti-6Al-0.4V-1.2Fe.
[0039] Figure 5 1 is a graph showing peak stress of alloy samples in examples of the present invention; wherein a is Ti-6Al-2.2V-0.6Fe; b is Ti-6Al-1.3V-0.9Fe; and c is Ti-6Al-0.4V-1.2Fe. DETAILED DESCRIPTION
[0040] In order to better understand the technical content of the present invention, specific embodiments are given and described below with reference to the accompanying drawings.
[0041] Various aspects of the present invention are described in this disclosure with reference to the accompanying drawings, in which a number of illustrative embodiments are shown. The embodiments of the present disclosure are not necessarily intended to be comprehensive. It should be understood that the various concepts and embodiments described above, as well as those described in more detail below, can be implemented in any of a number of ways.
[0042] Combine Figure 1 As shown, in an exemplary embodiment of the present invention, the design method of a low-cost, heat-processable titanium alloy includes the following steps:
[0043] (1) Establish Ti-6Al-xV-yFe alloy system.
[0044] (2) Establish the x, y and β stability coefficients (K β ) constraint relationship.
[0045] Kβ is the sum of the ratios of the concentrations of each β-stabilizing element to its critical concentration. In the Ti-6Al-xV-yFe alloy system, Kβ = x / C V +y / C Fe Therefore, from Table 1, we can see that Kβ=x / 15+y / 5.
[0046] Table 1 Critical concentrations of different alloying elements
[0047]
[0048] In order to make the Ti-6Al-xV-yFe alloy system meet the performance requirements of the Ti-6Al-4V alloy, the Kβ coefficient is controlled to be 0.27.
[0049] Therefore, we get formula (1):
[0050] 15K β =x+3y (1)
[0051] Where, x is the mass percentage of V element in Ti-6Al-xV-yFe alloy; y is the mass percentage of Fe element in Ti-6Al-xV-yFe alloy; K β is the β stability coefficient of Ti-6Al-xV-yFe alloy, and its value is 0.27.
[0052] (3) The Zener-Hollomon parameters were used to establish a relationship model between the average grain size of the alloy after hot working and the concentration of β-stabilizing elements and hot working parameters.
[0053] In titanium alloys, grain size is usually affected by hot working conditions (hot working temperature, strain rate) and alloy composition. Therefore, the Zener-Hollomon parameter is used to determine the relationship between the average grain size d of the alloy after hot working and the alloy composition x, y and hot working parameters (temperature T, strain rate ε), and the equation (2) is obtained:
[0054]
[0055] Where, d is the average grain size of the alloy after hot working, μm; d0 is the average grain size before hot working, μm; α is the recrystallization inhibition coefficient of the alloy element, ranging from 0.35 to 0.55; K β is the β stability coefficient of Ti-6Al-xV-yFe alloy, which is 0.27; Z0 is the reference Z parameter, which is 10 12 s -1 ;β is the strain rate sensitivity index; Where ε is the strain rate, s -1 ; Q is the deformation activation energy, J / mo; R is the gas parameter, J / (mol·K); T is the hot working temperature, K.
[0056] The relationship between deformation activation energy Q and x, y is shown in formula (3):
[0057] Q=340-15x 0.5 -25y+0.8xy (3)
[0058] (3) Combining the grain refinement strengthening and solid solution strengthening mechanisms, a mechanical property strengthening model is established, and formula (4) is obtained:
[0059] σ y =σ base +△σ soild +△σ Hall (4)
[0060] Where σ y is the yield strength of the required Ti-6Al-xV-yFe alloy;
[0061] σ base is the yield strength of the Ti-6Al matrix. It is understandable that this parameter is a technical parameter in the prior art and can be selected based on the data disclosed in the existing literature or obtained by sample preparation and testing according to the current experiment;
[0062] Δσ solid is the solid solution strengthening term, which is determined by formula (5):
[0063]
[0064] Where M is the Taylor factor, dimensionless; G is the shear modulus, GPa; b is the Burgers vector, nm; η i is the distortion coefficient of the solute element, dimensionless; c i is the concentration of the solute element, wt.%.
[0065] Δσ Hall is the Hall-Petch enhancement term, which is determined by formula (6):
[0066] △σ Hall =K d ×d -12 (6)
[0067] Where K d is the Hall-Petch coefficient, MPa·μm 1 / 2 ; d is the average grain size of the alloy after hot working, μm.
[0068] Combining equations (1)-(6), under the conditions of target hot working conditions and target yield strength, the values of x and y can be calculated, thereby completing the composition design optimization of the alloy.
[0069] It can be understood that the target hot working conditions in the present invention are the hot working temperature and strain rate to be adopted, and the hot working conditions will be set according to the actual equipment used or the needs in actual production; the target yield strength is the yield strength we expect the alloy to have. In order to meet the requirement of not changing the alloy properties, the yield strength of the Ti-6Al-4V alloy is used as the limit value in the present invention, and the yield strength of the designed Ti-6Al-xV-yFe alloy is not less than this limit value.
[0070] Therefore, as an optional example, the method for determining the target yield strength is as follows:
[0071] Substitute x=4, y=0 into the first, second, and third equations, and calculate the corresponding yield strength value σ1 under the target hot working conditions. The target yield strength σ y The value of is controlled within σ1+1≤σ yIt can be within the range of ≤σ1+10.
[0072] It can be understood that through the above design, the mechanical properties of the designed new alloy are comparable to those of the Ti-6Al-4V alloy, so that the new alloy still meets the application scenarios of the Ti-6Al-4V alloy, and the new alloy has better hot working performance without changing the Ti-6Al-4V alloy system.
[0073] In other optional examples, after obtaining the desired alloy, a series of alloys with different y values are designed based on the determined y value, and then the first equation, the second equation and the third equation are combined to obtain the corresponding yield strength under the same target hot working conditions, thereby selecting an alloy with optimal strength and optimal hot working performance.
[0074] For example, if y=0.3 is determined by calculation, y=0.1, 0.6, 0.9, 1.2... (x≥0, y≥0) are designed. Then the values of x and y are determined. Then, by combining equations (1)-(6), the corresponding yield strength is obtained under the same target hot working conditions. Since the thermoplastic properties of the alloy increase with the increase of iron content, the optimal alloy is the alloy corresponding to the maximum yield strength. This alloy has the optimal strength and the optimal hot working properties.
[0075] Therefore, through the above embodiment of the low-cost and easy-to-heat-process titanium alloy design method, on the one hand, a three-equation coupling model of β stability coefficient-grain size-mechanical properties is established through multi-physics field coupling modeling, which directly links the alloy composition (V, Fe content), hot working parameters (temperature, strain rate) with the microstructure (grain size) and mechanical properties (yield strength), forming a closed-loop design system. Compared with the traditional trial-and-error method, it avoids a large number of experimental trials and achieves a precise mapping from theoretical calculation to composition determination, significantly shortening the alloy development cycle. At the same time, the Zener-Hollomon parameters (used to describe the effect of temperature-strain rate on grain size during hot working) and the Hall-Petch strengthening model (used to determine the quantitative relationship between grain refinement and strength) are introduced, and the constitutive equation is constructed based on the classical theory of materials science to ensure that the physical meaning of the model is clear and the parameters are verifiable, thereby improving the scientificity and reliability of the design method.
[0076] The low-cost and easy-to-heat-process titanium alloy design method proposed in this invention optimizes the hot working performance while taking into account the strength and processing cost, providing an efficient and reliable engineering path for the development of titanium alloy materials. β) constrains the ratio of V and Fe elements, regulates the β phase stability of the alloy during hot working, reduces the deformation activation energy (Q), and thus improves thermoplasticity (such as reducing flow stress and inhibiting grain coarsening). Combined with the Z parameter model, the optimal composition combination can be directly calculated under the target hot working conditions (temperature, strain rate), avoiding problems such as processing cracking and high energy consumption caused by improper composition, and quantitatively improving the hot working performance. At the same time, focusing on Ti-6Al-based alloys, by adding low-cost elements Fe (to replace part of V), the alloy cost is reduced (the price of V is much higher than Fe) while maintaining the target yield strength (σy). At the same time, the model limits σ y It fluctuates slightly (σ1+1~σ1+10MPa) around the benchmark value (such as σ1 of Ti-6Al-4V) to ensure stable mechanical properties, avoid performance degradation due to composition adjustment, and achieve a balance between performance and cost.
[0077] For better understanding, the present invention is further described below with reference to several specific examples, but the preparation process is not limited thereto, and the content of the present invention is not limited thereto.
[0078] Unless otherwise specified, the materials in the examples were prepared according to existing methods or directly purchased from the market.
[0079] The following examples are all Ti-6Al-xV-yFe alloy systems.
[0080] Example 1
[0081] Take x = 4, y = 0, that is, Ti-6Al-4V alloy;
[0082] Target hot working conditions are: T = 1000 ° C, strain rate ε = 0.1s -1 ;
[0083] Other parameter values are: base The values are 780 MPa, M = 3.06, G = 42000 GPa, b = 0.295 × 10 -3 nm, K d =450MPa·μm 1 / 2 , η V =1.2,η Fe =3.5, initial grain size d0 = 50 μm; alloy parameters α = 0.45, β = 0.15, K β =0.27, R=8.314J / (mol·K), T=1273K, Z0=10 12 s -1 .
[0084] Under these conditions, combining equations (1)-(6), we obtain the yield strength σ1 of the Ti-6Al-4V alloy = 824.2 MPa.
[0085] The corresponding weight of grade 0 titanium sponge and Al-V alloy (45Al-55V) were taken and the cold crucible suspension melting method (the power was set to 120KW, the frequency was 25KHz, and the vacuum degree was 5×10 -3 Pa, melting temperature of 1750 ° C, holding time of 5 min, cooling water flow rate of 8 L / min), to prepare a final 1 kg ingot, in order to obtain a uniform alloy composition, six induction melting were performed to obtain Ti-6Al-4V alloy.
[0086] Example 2
[0087] Determine the target yield strength σ y =826.8MPa;
[0088] Target hot working conditions are: T = 1000 ° C, strain rate ε = 0.1s -1 ;
[0089] Other parameter values are: base The values are 780 MPa, M = 3.06, G = 42000 GPa, b = 0.295 × 10 -3 nm, K d =450MPa·μm 1 / 2 , η V =1.2,η Fe =3.5, initial grain size d0 = 50 μm; alloy parameters α = 0.45, β = 0.15, K β =0.27, R=8.314J / (mol·K), T=1273K, Z0=10 12 s -1 .
[0090] According to equations (1)-(6), x=3.1, y=0.3, and the corresponding alloy is Ti-6Al-3.1V-0.3Fe alloy.
[0091] The corresponding weights of grade 0 titanium sponge, high purity iron (99.85 wt.%) and Al-V alloy (45Al-55V) were weighed and smelted in a cold crucible suspension melting method (power setting of 120 kW, frequency of 25 kHz, vacuum degree of 5 × 10 -3 Pa, melting temperature of 1750 ° C, holding time of 5 min, cooling water flow rate of 8 L / min), to prepare a final 1 kg ingot, in order to obtain a uniform alloy composition, six induction melting were performed to obtain Ti-6Al-3.1V-0.3Fe alloy.
[0092] Example 3
[0093] [Ingredient test]
[0094] ICP-OES (Inductively Coupled Plasma Optical Emission Spectrometry) was used to test the composition of the samples. After testing, the final chemical compositions of the alloys of Examples 2-5 and Comparative Example 1 are shown in Table 2.
[0095] Table 2 Alloy chemical composition (wt.%)
[0096]
[0097] It can be seen from Table 2 that the samples prepared in Examples 1-2 meet their respective composition designs.
[0098] [Microstructure morphology]
[0099] The alloys of Example 1-2 were subjected to metallographic microscopic testing, and the results were as follows: Figure 2 shown.
[0100] As can be seen from the figure, the length of the α phase in Ti-6Al-4V is about 30.37μm and the width is about 4.25μm, showing a slender lamellar shape. The width of the β phase is only 0.11μm and it is distributed in the middle of the lamellar α phase. The aspect ratio of the α phase is 7.15, and the lamellar α phase and the β matrix form a directional cluster structure along the Burger orientation relationship, with obvious directionality.
[0101] When 0.3Wt.% Fe element is added, the length of the α phase in the structure is reduced to 24.38μm, the width is reduced to 3.03μm, and some fine equiaxed α phase appears, and cluster structures in different directions appear, indicating that the Fe content makes the grains of the alloy tend to be equiaxed, which can improve the anisotropy of the alloy.
[0102] [Mechanical properties test]
[0103] The mechanical properties of the alloys obtained in Examples 1 and 2 were tested, and the results are shown in Table 3.
[0104] Table 3
[0105]
[0106] As can be seen from Table 3, the yield strength of the alloy designed using the method of the present invention is comparable to that of the Ti-6Al-4V alloy and meets the target yield strength requirement (the difference between the actual value and the theoretical value is due to measurement error, but the trend is the same). In addition, the yield strength increases with the addition of iron, which is also confirmed by the results of the microstructure morphology.
[0107] [Thermoplastic performance verification]
[0108] The peak stress of the alloy obtained in Example 1-2 under different temperature and strain rate deformation conditions was obtained by hot compression test on Gleeble thermal simulation test machine. The results are as follows: Figure 3 shown.
[0109] It can be seen from the figure that for the Ti-6Al-3.1V-0.3Fe alloy under all deformation conditions, the increase in Fe content causes a significant decrease in the peak stress of the Ti-6Al-3.1V-0.3Fe alloy, that is, the Fe element has an obvious high-temperature softening effect on the Ti-6Al-3.1V-0.3Fe alloy.
[0110] At a deformation temperature of Tβ-250℃ and a strain rate of 10s -1 When the deformation temperature is Tβ-50℃ and the strain rate is 0.01s, the peak stress of Ti-6Al-4V is 458MPa, and the peak stress of Ti-6Al-3.1V-0.3Fe is 435MPa, with a decrease of 5%. -1 When the stress is 0.5 wt %, the peak stress of Ti-6Al-4V is 94 MPa, and the peak stress of Ti-6Al-3.1V-0.3Fe is 78 MPa, with a decrease of 17%.
[0111] Therefore, when the β stability coefficient Kβ remains consistent, the increase of Fe content will reduce the peak stress of Ti-6Al-xV-yFe alloy, causing a high-temperature softening effect on the thermoplastic properties of Ti-6Al-xV-yFe alloy, and this softening effect is also significantly related to the deformation temperature and deformation rate.
[0112] Example 4
[0113] Taking y = 0.6, then x = 2.2, that is, Ti-6Al-2.2V-0.6Fe alloy;
[0114] Target hot working conditions are: T = 1000 ° C, strain rate ε = 0.1s -1 ;
[0115] Other parameter values are: base The values are 780 MPa, M = 3.06, G = 42000 GPa, b = 0.295 × 10 -3 nm, K d =450MPa·μm 1 / 2 , η V =1.2,η Fe =3.5, initial grain size d0 = 50 μm; alloy parameters α = 0.45, β = 0.15, Kβ =0.27, R=8.314J / (mol·K), T=1273K, Z0=10 12 s -1 .
[0116] According to equations (1)-(6), the corresponding yield strength is 827.3 MPa.
[0117] The corresponding weights of grade 0 titanium sponge, high purity iron (99.85 wt.%) and Al-V alloy (45Al-55V) were weighed and smelted in a cold crucible suspension melting method (power setting of 120 kW, frequency of 25 kHz, vacuum degree of 5 × 10 -3 Pa, melting temperature of 1750 ° C, holding time of 5 min, cooling water flow rate of 8 L / min), to prepare a final 1 kg ingot, in order to obtain a uniform alloy composition, six induction melting were performed to obtain Ti-6Al-2.2V-0.6Fe alloy.
[0118] Example 5
[0119] Take y = 0.9, then x = 1.3, that is, Ti-6Al-1.3V-0.9Fe alloy;
[0120] Target hot working conditions are: T = 1000 ° C, strain rate ε = 0.1s -1 ;
[0121] Other parameter values are: base The values are 780 MPa, M = 3.06, G = 42000 GPa, b = 0.295 × 10 -3 nm, K d =450MPa·μm 1 / 2 , η V =1.2,η Fe =3.5, initial grain size d0 = 50 μm; alloy parameters α = 0.45, β = 0.15, K β =0.27, R=8.314J / (mol·K), T=1273K, Z0=10 12 s -1 .
[0122] According to equations (1)-(6), the corresponding yield strength is 827.3 MPa.
[0123] The corresponding weights of grade 0 titanium sponge, high purity iron (99.85 wt.%) and Al-V alloy (45Al-55V) were weighed and smelted in a cold crucible suspension melting method (power setting of 120 kW, frequency of 25 kHz, vacuum degree of 5 × 10 -3Pa, melting temperature of 1750 ° C, holding time of 5 min, cooling water flow rate of 8 L / min), and a final ingot of 1 kg was prepared. In order to obtain a uniform alloy composition, six induction melting processes were performed to obtain a Ti-6Al-1.3V-0.9Fe alloy.
[0124] Example 6
[0125] Take y = 1.2, then x = 0.4, that is, Ti-6Al-0.4V-1.2Fe alloy;
[0126] Target hot working conditions are: T = 1000 ° C, strain rate ε = 0.1s -1 ;
[0127] Other parameter values are: base The values are 780 MPa, M = 3.06, G = 42000 GPa, b = 0.295 × 10 -3 nm, K d =450MPa·μm 1 / 2 , η V =1.2,η Fe =3.5, initial grain size d0 = 50 μm; alloy parameters α = 0.45, β = 0.15, K β =0.27, R=8.314J / (mol·K), T=1273K, Z0=10 12 s -1 .
[0128] According to equations (1)-(6), the corresponding yield strength is 826.7 MPa.
[0129] The corresponding weights of grade 0 titanium sponge, high purity iron (99.85 wt.%) and Al-V alloy (45Al-55V) were weighed and smelted in a cold crucible suspension melting method (power setting of 120 kW, frequency of 25 kHz, vacuum degree of 5 × 10 -3 Pa, melting temperature of 1750 ° C, holding time of 5 min, cooling water flow rate of 8 L / min), and a final ingot of 1 kg was prepared. In order to obtain a uniform alloy composition, six induction melting processes were performed to obtain Ti-6Al-0.4V-1.2Fe alloy.
[0130] Example 7
[0131] [Ingredient test]
[0132] The samples were tested for composition using ICP-OES (Inductively Coupled Plasma Optical Emission Spectrometry). The final chemical compositions of the alloys of Examples 4-6 were as shown in Table 4.
[0133] Table 4 Alloy chemical composition (wt.%)
[0134]
[0135] It can be seen from Table 4 that the samples prepared in Examples 4-6 meet their respective composition designs.
[0136] [Microstructure morphology]
[0137] The alloys of Examples 4-6 were subjected to metallographic microscopic testing, and the results were as follows: Figure 4 shown.
[0138] It can be seen from the figure that when the Fe addition is 0.6wt.%, the length of the α phase is 15.57μm, the width is 2.72μm, and the aspect ratio of the α phase is 5.72; when the Fe content increases to 0.9wt.%, the length of the α phase is 10.32μm, the width is 3.06μm, and the content of the β matrix increases; as the Fe content increases to 1.2wt%, the length of the α phase is 9.05μm, the width is 4.39μm, the width of the β phase increases to 0.32μm, and the aspect ratio of the α phase is 2.06.
[0139] Combine Figure 2 Compared with Ti-6Al-4V, the width of the α phase in Ti-6Al-0.4V-1.2Fe increased slightly, but the length decreased by 70.2%, with a significant decrease. The proportion of equiaxed α phase in the microstructure further increased, and the aspect ratio of the α phase decreased by 71.1%. The alloy showed an obvious equiaxed trend, and the width of the β phase gradually increased.
[0140] It can be seen from the above results that the alloy designed by the method of the present invention has the same K β Under the coefficient, with the increase of Fe content, the grains of the alloy tend to be more and more equiaxed, but the phase ratio does not change much. The width of the α phase does not change much when the V and Fe content are fine-tuned, so the corresponding yield strength will not change much.
[0141] [Thermoplastic performance verification]
[0142] The peak stresses of the alloys obtained in Examples 1-4 and Comparative Example 1 under different temperature and strain rate deformation conditions were obtained by hot compression tests on a Gleeble thermal simulation tester. Figure 5 shown.
[0143] Combine Figure 3 and Figure 5As shown in the figure, for the Ti-6Al-xV-yFe series alloys under all deformation conditions, the increase of Fe content causes the peak stress of Ti-6Al-xV-yFe alloy to decrease significantly, that is, the Fe element has an obvious high-temperature softening effect on Ti-6Al-xV-yFe alloy.
[0144] At a deformation temperature of Tβ-250℃ and a strain rate of 10s -1 When the Fe content increases to 1.2Wt.%, the peak stress of Ti-6Al-0.4V-1.2Fe is 416MPa, with a decrease of 9.39%. When the deformation temperature is Tβ-50℃ and the strain rate is 0.01s -1 When , the peak stress of Ti-6Al-4V is 94MPa, and the peak stress of Ti-6Al-0.4V-1.2Fe is 37MPa, with a decrease of 61.29%.
[0145] Therefore, it is proved again that when the β stability coefficient Kβ remains consistent, the increase of Fe content will reduce the peak stress of Ti-6Al-xV-yFe alloy, resulting in a high-temperature softening effect on the thermoplastic properties of Ti-6Al-xV-yFe alloy, and this softening effect is also significantly related to the deformation temperature and deformation rate.
[0146] Thus, the best alloy can be selected as Ti-6Al-1.3V-0.9Fe alloy by combining yield strength and thermoplasticity.
[0147] From the above, it can be seen that the method of the present invention can directly complete the design of the alloy under the target hot working conditions and the target mechanical strength conditions of the alloy through the established equation, avoiding the disadvantage of using a series of experiments to explore the amount of Fe element addition. The obtained alloy can improve the hot working performance of the titanium alloy without changing the alloy properties, shorten the processing flow of the titanium alloy, and reduce the hot working cost of the titanium alloy.
[0148] While the present invention has been disclosed above with reference to preferred embodiments, this is not intended to limit the present invention. Persons skilled in the art will readily appreciate that various modifications and variations can be made without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be determined by the claims.
Claims
1. A design method for a low-cost, heat-processable titanium alloy, characterized in that: The following steps are involved: Establish the Ti-6Al-xV-yFe quaternary alloy system; then The constraint relationship between the concentration of β-stabilizing elements and the β-stabilizing coefficient in Ti-6Al-xV-yFe alloy was established, and the first equation was obtained; The Zener-Hollomon parameters were used to establish the relationship model between the average grain size of Ti-6Al-xV-yFe alloy after hot working and the concentration of β-stabilizing elements and hot working parameters, and the second equation was obtained; The mechanical property strengthening model was established by combining the grain refinement strengthening and solid solution strengthening mechanisms, and the third equation was obtained; According to the target yield strength and the target hot working conditions, the first equation, the second equation and the third equation are combined to obtain the corresponding concentration of the β-stabilizing element, thereby obtaining the desired titanium alloy.
2. The design method of low-cost and heat-processable titanium alloy according to claim 1, characterized in that: The first equation is shown in formula (1): Where, x is the mass percentage of V element in Ti-6Al-xV-yFe alloy; y is the mass percentage of Fe element in Ti-6Al-xV-yFe alloy; K β is the β stability coefficient of Ti-6Al-xV-yFe alloy, and its value is 0.
27.
3. The design method of low-cost heat-processable titanium alloy according to claim 1, characterized in that: The second equation is shown in formula (2): Where, d is the average grain size of the alloy after hot working, μm; d0 is the average grain size before hot working, μm; α is the recrystallization inhibition coefficient of the alloy element, ranging from 0.35 to 0.55; K β is the β stability coefficient of Ti-6Al-xV-yFe alloy, which is 0.27; Z0 represents the reference Z parameter, which is 10 12 s -1 ;β represents the strain rate sensitivity index; Where ε is the strain rate, s -1 ; Q is the deformation activation energy, J / mo; R is the gas parameter, J / (mol·K); T is the hot working temperature, K.
4. The design method of low-cost heat-processable titanium alloy according to claim 3, characterized in that: The relationship between the deformation activation energy Q and x, y is set as shown in formula (3): Q=340-15x 0.5 -25y+0.8xy (3)。 5. The design method of low-cost heat-processable titanium alloy according to claim 1, characterized in that: The third-party equation is shown in formula (4): s y =s base +△σ soild +△σ Hall (4) Where, σ y is the yield strength of the required Ti-6Al-xV-yFe alloy, MPa; σ base is the yield strength of Ti-6Al matrix, MPa; Δσ solid is the solid solution strengthening term, MPa; Δσ Hall is the Hall-Petch strengthening term, MPa.
6. The design method of low-cost heat-processable titanium alloy according to claim 5, characterized in that: The solid solution strengthening term Δσ solid Determine by formula (5): Where M is the Taylor factor, dimensionless; G is the shear modulus, GPa; b is the Burgers vector, nm; η i is the distortion coefficient of the solute element, dimensionless; c i is the concentration of the solute element, wt.%.
7. The design method of low-cost heat-processable titanium alloy according to claim 5, characterized in that: The Hall-Petch enhancement term Δσ Hall Determine by formula (6): △σ Hall =K d ×d -12 (6) Where K d is the Hall-Petch coefficient, MPa·μm 1 / 2 ; d is the average grain size of the alloy after hot working, μm.
8. The design method of low-cost heat-processable titanium alloy according to claim 1, characterized in that: The target yield strength is determined as follows: Substitute x=4, y=0 into the first, second, and third equations, and calculate the corresponding yield strength σ1 under the target hot working conditions. The target yield strength σ y The value of is controlled within σ1+1≤σ y The result is within the range of ≤σ1+10.
9. The design method of low-cost heat-processable titanium alloy according to claim 1, characterized in that: After obtaining the required alloy, a series of alloys with different y values are designed based on the determined y value. Then, the first equation, the second equation, and the third equation are combined to obtain the corresponding yield strength under the same target hot working conditions, and the alloy with the optimal strength and optimal hot working performance is selected.